2012
DOI: 10.3892/or.2012.1792
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous expression of UHRF1 promotes proliferation and metastasis of breast cancer cells

Abstract: Abstract. In the present study, we investigated the role of UHRF1 (ubiquitin-like protein containing PHD and RING finger domains 1) in proliferation, invasion and migration of breast cancer cells, and the potential mechanisms were also explored. Cell proliferation was examined by 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay; cell cycle distribution and apoptosis were evaluated using flow cytometry; protein expression was determined by western blotting; angiogenesis of xenografts wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 16 publications
0
37
0
Order By: Relevance
“…Furthermore, the overexpression of UHRF1 destabilizes and delocalizes DNMT1, and causes DNA hypomethylation in cancer cells (19). Although several studies have demonstrated the function of UHRF1 in tumorigenesis and tumor progression (14,17,20), little is known regarding the function of UHRF1 in human osteosarcoma cells. In the present study, the expression of UHRF1 was detected in all of the human osteosarcoma cell lines examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the overexpression of UHRF1 destabilizes and delocalizes DNMT1, and causes DNA hypomethylation in cancer cells (19). Although several studies have demonstrated the function of UHRF1 in tumorigenesis and tumor progression (14,17,20), little is known regarding the function of UHRF1 in human osteosarcoma cells. In the present study, the expression of UHRF1 was detected in all of the human osteosarcoma cell lines examined.…”
Section: Discussionmentioning
confidence: 99%
“…Through interaction with other nuclear proteins, including Tip60, histone deacetylase and G9A, UHRF1 may function as a bridge between DNA methylation and the histone methylation (12). Furthermore, significant overexpression of UHRF1 has been observed in several types of human tumor, including breast (13,14), bladder (15), prostate (16) and lung cancer (17). The overexpression of UHRF1 has also been reported to reduce the radiosensitivity of human breast cancer cells and HeLa cells to γ-irradiation (18).…”
Section: Introductionmentioning
confidence: 99%
“…Up-regulations of UHRF1 were observed in various cancer cells, including breast, prostate, and lung cancer (24,34,35). In cancer cells, UHRF1 plays a key role in promoting proliferation, and its abundance remains at high levels in all phases of the cell cycle (24,31,36,37). Thus, UHRF1 is a potential drug target for cancer therapy and a biomarker for diagnosis (38).…”
mentioning
confidence: 99%
“…It was found that UHRF1 could promote the G1/S transition as a direct target of E2F1, which is a transcriptional factor essential for S-phase entry [30]. In examining many human cancers, including lung cancer, breast cancer and colorectal cancer [31,32,33], we have found that UHRF1 could promote their proliferation and metastasis.…”
Section: Discussionmentioning
confidence: 99%